Manipulation of focal patterns in acoustic Soret type zone plate lens by using reference radius/phase effect; Ultrasonics; Vol. 91 - Tarrazo-Serrano D. Daniel; Rubio C. Constanza; Minin O. V. Oleg Vladilenovich; Candelas P/ Pilar; Minin I. V. Igor Vladilenovich (2019, 2019)
Title screen